Temperature dependence of the energy resolution of a gallium arsenide detector - Nassurlla, Maulen; Burtebayev, N.; Mukhashev, K.M.; Nassurlla, Marzhan; Khojayev, R.A. (Recent Contributions to Physics, 2018)
The paper presents the results of the study of the detector, made by gas-phase epitaxy technology of high purity gallium arsenide (VPE GaAs). The energy resolution of the detector is 52 KeV. For all detectors under study, the efficiency of charge collection from the longest-running particles reaches a maximum at a voltage of 60 V. At zero offset, the charge collection efficiency for alpha-particle energies from 4.8 to 7.7 MeV ranges from 74 to 58%. This data show the possibility of using the developed detectors in the particles counting mode without external offset with high collection efficiency as a sensor of recoil protons for detecting fast neutrons. Detector saves spectrometric qualities to a temperature of 110 °C while increasing the operating offset to 110-130 V. A further increase in temperature to 130 °C leads to a catastrophic degradation of detector characteristics.